Critical Thinking Ability of Junior High School Students in Solving Mathematics Problems Viewed from Reflective-Impulsive Cognitive Style - Afifah, Nur Wanda; Rahaju, Endah Budi (Universitas Negeri Surabaya, 2025)
One goal of learning mathematics in Permendikbud No. 58 of 2013 is that students have the critical thinking ability. Apart from critical thinking ability, another goal of learning mathematics is to solve mathematical problems. Critical thinking ability is needed in the problem solving process. In solving problems, students will use various strategies. Problem solving strategies are heavily influenced by cognitive styles. One challenging problem that can give students the opportunity to use all their abilities, including critical thinking ability, is a problem related to geometry in the material of flat sided spaces. This research is a qualitative descriptive study. The subjects of this study were two students of class VIII-H at Junior High School in Surabaya of the same sex, who had learned flat sided space, had equivalent mathematical abilities, had good communication skills, and had reflective and impulsive cognitive style. The method of collecting data in this study is through Matching Familiar Figure Test (MFFT), math ability tests, problem solving tests, and interviews. The results showed that reflective cognitive style students have very good critical thinking ability focus, reason, inference, situation, clarity in the steps of understanding the problems, devise a plan, and carrying out the plan. Meanwhile, in the step of looking back, student with a reflective cognitive style have good overview critical thinking ability. Impulsive cognitive style students have very good critical thinking ability reason, inference, situation, clarity in the steps of devise a plan and solving problems according to plan. Meanwhile, in the step of understanding the problem, student with an impulsive cognitive style has well enough focus critical thinking ability. In step of looking back student with an impulsive cognitive style have good overview critical thinking ability.